Peranan Zakat Sebagai Strategi Dakwah dalam Pemberdayaan Ekonomi pada Masa Pandemi Covid-19 - Zulhendra Zulhendra; Acep Aripudin (Jurnal Iman dan Spiritualitas, 2021)
Zakat is one of the five pillars of Islam that must be fulfilled by every individual Muslim if he fulfills the conditions that must be issued. When viewed from the spiritual aspect, the practice of tithing can purify the soul and property. During the COVID-19 pandemic, of course, the role of zakat as a da'wah strategy in economic empowerment has an important role, one of which is at the Miftahul Jannah Mosque, Sindang Pakuon Village, District, Cimanggun, Sumedang Regency in managing zakat Fitrah during the pandemic period. The research method used is a qualitative method. The results of this study indicate that the da'wah strategy in zakat fitrah is aimed at the poor or there are Covid with the help of money and rice, and for the da'i as a da'wah interpreter is with staple food.